PERAN KANTOR PERTANAHAN KABUPATEN PELALAWAN DALAM MENYELESAIKAN SENGKETA KEPEMILIKAN TANAH DI KABUPATEN PELALAWAN - Syaprianto, Syaprianto; Adni, Dita Fisdian (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
This study aims to look at the role of the Pelalwan District Land Office in resolving land ownership disputes in Pelalawan Regency and this research was conducted using survey research methods, the level of exploration is descriptive and using qualitative data analysis. The researcher interviewed directly and in depth with key informants who were considered to be most aware of the role of the Land Office in resolving land ownership disputes using a technique. purposive sampling. The results of this study indicate that the role of the Land Office in resolving disputes Land ownership is considered quite maximal because it has become a mediator between the two parties to the dispute in conducting mediation even though it has not yet met an agreement and there are several findings that have become obstacles to the Land Office in resolving land ownership disputes. First, the Land Office lacks human resources. Second, Lack of witnesses Regarding Land History and third, Factors of disputing character that are only selfish.